1995
DOI: 10.1046/j.1469-0705.1995.05020098.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of the two‐vessel cord: implications for patient counselling and obstetric management

Abstract: The study was designed to investigate the implications of the sonographic diagnosis of the two-vessel umbilical cord for patient counselling and pregnancy management. Retrospective analysis was carried out of prenatal findings and pregnancy outcomes when a two-vessel cord was diagnosed in utero. Eighty-two fetuses each with a single umbilical artery were diagnosed by ultrasound. Ten were aneuploid, including nine with visible structural defects and one with early onset intrauterine growth retardation. Of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
62
1
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 0 publications
6
62
1
7
Order By: Relevance
“…This rate of anomalous conditions is similar to that found in prior studies by Catanzarite and coworkers 8,9 but is considerably higher than the rate found in several other studies. [5][6][7] When an isolated SUA is identified on a prenatal sonogram, the parents should be counseled about the significance of this finding.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This rate of anomalous conditions is similar to that found in prior studies by Catanzarite and coworkers 8,9 but is considerably higher than the rate found in several other studies. [5][6][7] When an isolated SUA is identified on a prenatal sonogram, the parents should be counseled about the significance of this finding.…”
supporting
confidence: 90%
“…Other authors, however, have found a far higher frequency of anomalies or aneuploidy in neonates with a prenatal sonographic diagnosis of isolated SUA. 8,9 In these two reports, five of 56 neonates (9%) with apparently isolated SUA at prenatal sonography were found to be abnormal at birth. We undertook a study of prenatally diagnosed SUA to assess the frequency, nature, and sonographic detection of anomalies.…”
mentioning
confidence: 90%
“…Although the umbilical cord can be easily visualized on prenatal sonogram, there is a discrepancy between the theoretic ultrasound accuracy and actual reliability to detect SUA reflected in the range of positive predictive values of 65 to 94%. 25,27 Due to lower than expected ultrasound detection of SUA, there is a discrepancy in number of neonates born with an SUA and associated anomaly diagnosed postnatally compared to those in the antenatal period. The proportion of identified fetuses with associated malformations diagnosed prenatally would rise postnataly from 26 and 43 to 43% and 50%, respectively.…”
Section: Number Of Umbilical Cord Vesselsmentioning
confidence: 99%
“…The proportion of identified fetuses with associated malformations diagnosed prenatally would rise postnataly from 26 and 43 to 43% and 50%, respectively. 27,28 In addition to associated fetal anomalies with an SUA, an intrauterine fetal growth restriction (IUGR) was observed more frequently in aneuploid than euploid fetuses, 28% vs 15-20%, respectively.…”
Section: Number Of Umbilical Cord Vesselsmentioning
confidence: 99%
See 1 more Smart Citation